Machine-washable and breathable pressure sensors based on triboelectric nanogenerators enabled by textile technologies. (April 2020) - Zhao, Zhizhen; Huang, Qiyao; Yan, Casey; Liu, Youdi; Zeng, Xiangwen; Wei, Xiaoding; Hu, Youfan; Zheng, Zijian
Abstract: Utilization of textile's triboelectric effect to realize the perception of pressure is of great interest for self-powered wearable electronics that integrate seamlessly with smart fabrics. However, the challenges associated with rational material/device designs based on conventional textile structures and the lack of understanding of the mechanical circumstances experienced by textile devices hamper the further advancement of this technology. Here, textile pressure sensors based on triboelectric nanogenerators (TENGs) with machine washability and excellent breathability are manufactured by using machines to interlace robust Cu-coated polyacrylonitrile (Cu-PAN) yarns and parylene coated Cu-PAN (parylene-Cu-PAN) yarns via multiple textile industry compatible technologies for the first time, simultaneously achieving devices with stitched, woven, and knitted structures. TENG-based pressure sensors with different textile structures are investigated under as-fabricated conditions and after machine washing, and a relation is proposed between textile structure and the key characteristics of the sensors. The material/device designs, mechanical circumstances, manufacturing methods, etc., will affect the sensitivity, linearity, saturation trend and washability of the obtained sensors. Finally, a smart textile glove with stitched pressure sensors is made to demonstrate grip posture detection in various circumstances. Graphical abstract: Triboelectric nanogenerator-based, machine-washable textile pressure sensors are manufactured using machines via multiple textile industry compatible technologies for the first time, simultaneously achieving devices with stitched, woven, and knitted structures, and the relation between textile structure and the key characteristics of the sensors is revealed. Image 1 Highlights: TENG-based textile pressure sensors are manufactured by adopting multiple textile manufacturing technologies via machine. Understanding of the effects of design, mechanical circumstances and manufacturing methods on the textile sensors' behaviors. Pressure sensors with different textile structures are investigated under as-fabricated conditions and after machine washing.